Effects of problem-based learning on cognitive performance, mathematical values and motivation to learn mathematics among secondary school students in Malaysia - Ramli, Fatimah (2018)
This study examined the effectiveness of implementing Problem Based learning (PBL) strategy on the students’ cognitive performance, mathematical values and motivation in learning mathematics for Form two secondary school students.. A quasi-experimental nonrandomized control group post-tests design was conducted consists of 62 students on two intact groups. 35 students were placed in the experimental group while 27 students in the control group participated in this study. Students in the experimental group underwent Problem Based Learning instruction strategy (PBL), while the control group learned mathematics using conventional instruction strategy (CI) in class over a period of eight weeks. Problem-based learning strategy refers to the use of problem-based learning modules in teaching and learning mathematics. Form two students from one of schools in Selangor were the sample of the study. Four instruments were used in this study namely, Achievement Test, Paas Mental Effort Rating Scale, ARCS motivation survey and mathematical values scoring rubric. Achievement test and Paas Mental Effort Rating Scale were used to measure cognitive performance. Students’ mathematical values were measured using a set of rubrics consist of nine mathematics educational values while ARCS motivation survey were used to measure students’ motivation toward learning mathematics. The data were analysed using one-way between-group analyses of covariance (ANCOVA) and independent t-test. The results of this study showed that students who were exposed to the PBL strategies achieved significantly better achievement scores with less mental effort as compared to those who were taught using the CI strategy. Similar findings also showed the PBL strategies helped students achieved better scores in solving higher order questions compared to the CI strategy group. However, there were no significantly different scores in solving the lower order questions between the two groups. The students from the PBL strategy group acquired significantly higher scores than the CI strategy group in the overall mathematical values in the subscales of accuracy, conjecturing, consistency, creativity, effective organization, efficient working/strategies, persistence, and systematic working. The result also indicated that PBL strategy also induced higher level of overall motivation towards learning in the subscale of attention, relevance and confidence as compared to CI strategy. Therefore, the study shows that the PBL strategy enhanced students’ cognitive performance, students’ mathematical values and students’ motivation in learning mathematics. These findings indicated that the problem based learning instruction is superior in comparison to the CI strategy, hence implying PBL strategy in teaching and learning of mathematics was more efficient than the CI strategy. The results from this study suggested the using of problem based learning strategy in the teaching and learning topics of Pythagoras theorem, Transformation, Solid Geometry II is beneficial and the utilization of this strategy should be continued. Therefore, it is recommended that by using PBL strategy would help to enhanced students’ cognitive performance, mathematical values and motivation better as compared to CI strategy.